Royal Thinking Style among Postgraduate Students - Adnan, Abdullah Raad; Fadel, Rana Zuhair (Journal of Tikrit University for Humanities, 2023)
The primary objective of the present research is to ascertain the cognitive processes and patterns of thinking shown by postgraduate students. The objective of this study is to determine whether there are statistically significant variations in the cognitive thinking style of postgraduate students based on the gender variable (male-female). The objective of this study is to determine whether there are statistically significant changes in the cognitive thinking style of postgraduate students based on their area of expertise, namely in the fields of scientific and human disciplines. In order to fulfill the aims of the research, the investigator used the scale developed by Al-Mamouri (2018) to assess the royal thinking style among a selected group of postgraduate students. Upon engaging in postgraduate studies, the researcher used two research methodologies and then conducted statistical analysis on the collected data using the Statistical Package for the Social Sciences (SPSS). Consequently, the study yielded the following findings: The postgraduate students at the University of Tikrit exhibit a distinct mode of thinking that is shared by individuals of both genders and across many academic specialties. Based on the findings, the study has generated many suggestions and ideas.